2005
DOI: 10.1007/s10397-005-0098-4
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic management of a cornual ectopic pregnancy

Abstract: There are various possibilities for treating cornual ectopic pregnancies, including medical approaches using methotrexate and surgical approaches using laparoscopy. This report describes the laparoscopic management of a large cornual ectopic pregnancy associated with a high b-human chorionic gonadotropin level and reviews the techniques and outcomes of conservative treatment described in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…Tratamiento quirúrgico. El tratamiento tradicional ha sido la histerectomía o resección cornual por laparotomía (3,6,10,11,13,14,19,(22)(23)(24)(26)(27)(28)(29)31,32), sin embargo, con el advenimiento de la ecografía y la βCG (3,11,19) se realizan diagnósticos más tempranos y ha permitido escoger nuevas alternativas menos agresivas para el tratamiento.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Tratamiento quirúrgico. El tratamiento tradicional ha sido la histerectomía o resección cornual por laparotomía (3,6,10,11,13,14,19,(22)(23)(24)(26)(27)(28)(29)31,32), sin embargo, con el advenimiento de la ecografía y la βCG (3,11,19) se realizan diagnósticos más tempranos y ha permitido escoger nuevas alternativas menos agresivas para el tratamiento.…”
Section: Resultsunclassified
“…Histeroscopia. La histeroscopia también ha sido reportada para el tratamiento del embarazo ectópico cornual (20,29). Sanz y cols (36), reportan el uso de la histeroscopia para romper un saco persistente después del tratamiento con metotrexato y realizan bajo visión ecográfica la extracción del tejido placentario.…”
Section: Resultsunclassified
“…Buxant et al reported using the classical laparoscopic method of incising the cornual area after a transparietal Xylocaine-adrenaline injection, draining the contents and suturing the area [9]. However, they also used a post-operative systemic methotrexate injection [9]. Moon et al described the vasopressin electric cauterisation method, the endoloop before evacuation of conceptus method and the encircling suture before evacuation of conceptus method [8].…”
Section: Discussionmentioning
confidence: 97%
“…Buxant et al reported using the classical laparoscopic method of incising the cornual area after a transparietal Xylocaine-adrenaline injection, draining the contents and suturing the area [9]. However, they also used a post-operative systemic methotrexate injection [9].…”
Section: Discussionmentioning
confidence: 99%